The role of POPX2 in the regulation of hippo pathway - Muhammad Bakhait Rahmat (2018)
The Hippo pathway has gained immense attention due to its key role in regulating organ size as well as its relevance to tissue regeneration and cancer. The pathway is renowned for regulating the two transcriptional co-activators, YAP and TAZ, which are key players for cell proliferation, organogenesis, and maintenance of tissue-specific progenitor cells during tissue renewal and regeneration. During tumorigenesis YAP/TAZ reprogram cancer cells into cancer stem cells in addition to their involvement in tumor initiation, progression and metastasis. Not surprisingly, in the past few years, intense focus has been shown on YAP and TAZ as potential therapeutic targets in the study of cancer and regenerative medicine. Herein, we investigate the role of POPX2 in the regulation of YAP/TAZ transcriptional co-activators through the Hippo pathway. We found that POPX2 interacts with several of the Hippo pathway core kinases, including LATS1 which is the direct kinase regulating YAP/TAZ. We also demonstrated that POPX2 could dephosphorylate LATS1, on Threonine-1079, the site required for LATS1 activity. Furthermore, CRISPR knock-out of POPX2 in the highly invasive breast cancer cell line MDA-MB-231, X2KO cells, showed lower YAP/TAZ protein levels both in the cytoplasm as well as in the nucleus. When the X2KO cells are grown under low attachment condition, YAP/TAZ is lost from the nucleus, suggesting that POPX2 is required for YAP/TAZ nuclear retention. RT-PCR analysis on selected YAP/TAZ target genes, CTGF and ANKRD1, showed that the transcript levels of these genes are lower in the X2KO cells. These results support possible roles of POPX2 in YAP/TAZ stabilization. Consistent with these observations, loss of POPX2 further leads to the decrease in cell proliferation and anchorage independence growth, which phenocopies the loss of YAP/TAZ.